2016
DOI: 10.1021/acs.est.5b06158
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Species Extrapolation of Uptake and Disposition of Neutral Organic Chemicals in Fish Using a Multispecies Physiologically-Based Toxicokinetic Model Framework

Abstract: The potential to bioconcentrate is generally considered to be an unwanted property of a substance. Consequently, chemical legislation, including the European REACH regulations, requires the chemical industry to provide bioconcentration data for chemicals that are produced or imported at volumes exceeding 100 tons per annum or if there is a concern that a substance is persistent, bioaccumulative, and toxic. For the filling of the existing data gap for chemicals produced or imported at levels that are below this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 52 publications
2
50
0
1
Order By: Relevance
“…PBPK models have been published for adult zebrafish, mostly for ecotoxicological risk assessment [18][19][20]. Recently, Brox et al [21] used a one-compartment two-parameter model developed by Gobas and Zhang [22] to explore the impact of physicochemical properties of polar compounds and of biological processes on embryo concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…PBPK models have been published for adult zebrafish, mostly for ecotoxicological risk assessment [18][19][20]. Recently, Brox et al [21] used a one-compartment two-parameter model developed by Gobas and Zhang [22] to explore the impact of physicochemical properties of polar compounds and of biological processes on embryo concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…This difference cannot be explained by the simplicity of the applied model. While increasing the model complexity generally improves model performance ( Rowland et al, 2017 ), and more sophisticated Physiologically Based Toxicokinetic (PBTK) models have already been developed for adult stages of zebrafish ( Péry et al, 2014 ; Brinkmann et al, 2016 ), no approach has, as of yet, been proposed for fish larval stages, for which chemical internal distribution differs. It has, however, been shown that the one-compartment model applied here is in agreement with the PBTK models regarding the prediction of chemical concentrations in whole fish ( Stadnicka et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of such models have been developed over the last decade in human toxicology (e.g. [ 13 , 154 ]), but corresponding approaches are now emerging in fish toxicology as well [ 25 , 136 ].…”
Section: In Vitro Application Domains In Ecotoxicology: What Kind Of mentioning
confidence: 99%